2021
DOI: 10.1007/s10067-021-05631-9
|View full text |Cite|
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome in children during the COVID-19 pandemic in Turkey: first report from the Eastern Mediterranean

Abstract: Objective We aimed to describe the typical clinical and laboratory features and treatment of children diagnosed with multisystem inflammatory syndrome in children (MIS-C) and to understand the differences as compared to severe/critical pediatric cases with COVID-19 in an eastern Mediterranean country. Methods Children (aged <18 years) who diagnosed with MIS-C and severe/critical pediatric cases with COVID-19 and were admitted to hospital between March 26 and November 3, 2020 were enrolled in the study. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
9
22
0
2
Order By: Relevance
“…Given the recent data suggesting that geographical circumstances may influence the development of the disease, large cohort studies from every single country are required for better understanding. This study is the third reported cohort from Turkey, and owing to its larger sample size, it may present contributions to the previous ones [18,19]. Demographic findings of our study such as male predominance, prominently affected age group and survival rates were consistent with the current literature.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Given the recent data suggesting that geographical circumstances may influence the development of the disease, large cohort studies from every single country are required for better understanding. This study is the third reported cohort from Turkey, and owing to its larger sample size, it may present contributions to the previous ones [18,19]. Demographic findings of our study such as male predominance, prominently affected age group and survival rates were consistent with the current literature.…”
Section: Discussionsupporting
confidence: 89%
“…Although studies describing MIS-C patients so far present a wide variability of clinical signs, most of the cases had cardiac dysfunction and gastrointestinal symptoms [18,29]. Consistent with the previous reports, the two most common systemic involvements in our study were cardiac and gastrointestinal.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We read the article by Ozsurekci and colleagues with great interest [1]. The article examines the clinical and laboratory characteristics of 30 multisystem inflammatory syndrome in children (MIS-C) cases and provides valuable data for the literature.…”
mentioning
confidence: 99%
“…The article's discussion part refers to the literature, which describes that MIS-C develops a few weeks following exposure [1]. It is speculated that SARS-CoV-2 could have a more symptomatic course in infants below the age of 5.…”
mentioning
confidence: 99%